Aspirin Alleviates Particulate Matter Induced Asymptomatic Orchitis of Mice via Suppression of cGAS-STING Signaling - Zhu, Tengyu; Chen, Xue; Qiu, Huan; Liu, Yang; Mwangi, James; Zhao, Ling; Ding, Wenjun; Lai, Ren; Jin, Lin (Frontiers in Immunology, 2021)
As an important source of air pollutant, airborne particulate matter (PM) has become a major threat to public health. Orchitis is characterized by acute or chronic testicular inflammation and is a primary cause of male infertility. Although accumulating evidence indicates that PM exposure is associated with increased male infertility rates, the mechanism by which PM is involved is not well understood. Here, we found that short-term PM exposure activated NF-κB signaling in mouse Leydig cells and testes and leading to asymptomatic orchitis. Analyzing the mitochondrial abundance and cGAMP levels in PM exposed mouse Leydig cells, we found that PM exposure induced mitochondrial injury and mtDNA release, leading to inflammation via the cGAS-STING axis. We also found that aspirin-induced acetylation of cGAS inhibited the inflammation in mice after PM exposure, especially in the testes. Moreover, aspirin pretreatment rescued offspring growth in PM-exposed mice. In summary, our study not only provides evidence that PM-induced asymptomatic orchitis in mice may be amenable to aspirin pre-treatment by acetylating cGAS, but also provides a potential explanation for male infertility caused by air pollutants.